Advances in Neutralization Assays for SARS‐CoV‐2. (16th June 2021) - Lu, Yuying; Wang, Jin; Li, Qianlin; Hu, Huan; Lu, Jiahai; Chen, Zeliang
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has triggered a global health emergency and brought disaster to humans. Tremendous efforts have been made to control the pandemic, among which neutralizing antibodies (NAbs) are of specific interest to researchers. Neutralizing antibodies are generated within weeks after infection or immunization and can protect cells from virus intrusion and confer protective immunity to cells. Thus, production of NAbs is considered as a main goal for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccines and NAbs may be used for patient treatment in the form of monoclonal antibodies. Neutralization assays are capable of quantitatively detecting NAbs against SARS‐CoV‐2, allowing to explore the relationship between the level of NAbs and the severity of the disease, and may predict the possibility of re‐infection in COVID‐19 patients. They can also be used to test the effects of monoclonal antibodies, convalescent plasma and vaccines. At present, wild‐type virus neutralization assay remains the gold standard for measuring Nabs, while pseudovirus neutralization assays, Surrogate virus neutralization test (sVNT) and high‐throughput versions of neutralization assays are popular alternatives with their own advantages and disadvantages. In this review article, we summarize the characteristics and recent progress of SARS‐CoV‐2 neutralization assays. Special attention is given to the current limitations of various neutralization assays so as to promote new possible strategies with NAbs by which rapid SARS‐CoV‐2 serological diagnosis and antiviral screening in the future will be achieved.